PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS POKOK BAHASAN PENINGGALAN SEJARAH DI KELAS IV SD NEGERI 48 KOTA TERNATE - Dwi Arlitha Suyono Ciu; Rustam Hasim (PEDAGOGIK, 2021)
This study aims to improve students’ learning outcomes in the subject of social studies subject of historical heritage in class IV SD Negeri 48 Ternate, the type of research used is Classroom Action Research (CAR). The stages are (1) planning, (2) implementation and observation, and (3) reflection. The subjects of this study were 30 students. The object of this research is the inquiry learning model.The data collection technique in this study are observation sheets, tests, and documentation of the instruments used to determine student learning outcomes in the form of a multiple choice test (PG) with 10 numbers. The data analysis technique used is descriptive qualitative that is seen from several percent of the success rate of student learning outcomes.The results showed that in the first cycle and the first cycle, the application of the inquiry learning model could improve students’ learning outcomes in social studies subjects, especially the historical heritage material in class IV SD Negeri 48 Ternate. This shows the students' completeness in the first cycle as many as 10 students or 17.70% of the 30 students who took part in the learning process in the classroom with an average number of 59.00% in the first cycle. The second cycle of learning students’ learning outcomes an increase. Of the 30 students who took part in the learning process in the classroom, 28 students who completed it or 23.40% with an average score of 78.00%, or in the good category descriptive scale.